Deprivation of the Periplasmic Chaperone SurA Reduces Virulence and Restores Antibiotic Susceptibility of Multidrug-Resistant Pseudomonas aeruginosa - Klein, Kristina; Sonnabend, Michael S.; Frank, Lisa; Leibiger, Karolin; Franz-Wachtel, Mirita; Macek, Boris; Trunk, Thomas; Leo, Jack C.; Autenrieth, Ingo B.; Schütz, Monika; Bohn, Erwin (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa (Pa) is one of the main causative agents of nosocomial infections, especially in immunocompromised patients, and the spread of multidrug-resistant strains of Pa is rising. Therefore, novel strategies for therapy are urgently required. The outer membrane composition of Gram-negative pathogens and especially of Pa restricts the efficacy of antibiotic entry into the cell and determines virulence. For efficient outer membrane protein biogenesis, the BAM complex in the outer membrane and chaperones like Skp and SurA within the periplasm are crucial. Previous studies indicated that the importance of individual proteins involved in OMP biogenesis may vary between different Gram-negative species. In addition, since MDR resistant Pa pose a serious global threat, the interference with both virulence and antibiotic resistance -as it could be accomplished by disturbing OMP biogenesis- might be a new strategy to cope with this challenge. To this end, deletion mutants of the non-essential BAM complex components BamB and BamC, of the periplasmic chaperone and Skp homolog HlpA as well as a conditional deletion mutant of the periplasmic chaperone SurA were created and tested for antibiotic sensitivity and virulence. The most profound effects for both traits were associated with a lack of SurA, characterized by increased membrane permeability, enhanced sensitivity to antibiotic treatment and attenuation of virulence in a Galleria mellonella infection model. Strikingly, the conditional deletion of surA in a multidrug-resistant clinical bloodstream isolate re-sensitized the strain to treatment with antibiotics to which the strain was resistant before. From our data we conclude that SurA of Pa serves as a promising target to develop antiinfective drugs or drugs that could be used as sensitizers in combination with available antibiotics.